2011
DOI: 10.2176/nmc.51.630
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Diagnosis of Intramedullary Spinal Schwannomas

Abstract: Intramedullary spinal schwannomas are rare benign spinal cord tumors and are easily misdiagnosed because of the imaging characteristics shared with intramedullary glioma. Correct preoperative definitive diagnosis is essential for treatment and prognosis. To improve the preoperative diagnostic strategy, clinical and imaging data of seven patients with intramedullary spinal schwannoma (6 men, mean age 44 years, mean duration of illness 4.2 years) treated in our department between 2003 and 2010 were collected and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 13 publications
3
21
0
Order By: Relevance
“…[ 5 ] Earlier studies have indicated a male predominance (our patient was a male) for IS,[ 5 ] though a recent study showed no sex predilection. [ 6 7 ] The mean age at presentation for these tumors is 49.2 years, similar to our patient aged 48 years. [ 7 ]…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…[ 5 ] Earlier studies have indicated a male predominance (our patient was a male) for IS,[ 5 ] though a recent study showed no sex predilection. [ 6 7 ] The mean age at presentation for these tumors is 49.2 years, similar to our patient aged 48 years. [ 7 ]…”
Section: Discussionsupporting
confidence: 77%
“…[ 6 7 ] The mean age at presentation for these tumors is 49.2 years, similar to our patient aged 48 years. [ 7 ]…”
Section: Discussionsupporting
confidence: 74%
“…The mean postoperative follow-up period was 56 months, with no neurologic deterioration or recurrence. 38 Yang et al analyzed 20 cases of intramedullary schwannoma that were diagnosed in their hospital from 2000 to 2013, including 7 cases that were reported by Wu et al in 2011, but with a longer follow-up period (►Table 1). They also encountered 1,320 patients with intramedullary lesions (ependymomas, astrocytomas, and hemangioblastomas) and 1,723 patients with intraspinal schwannomas during the same period.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, intramedullary ependymal cysts have not previously been reported in association with schwannomas. Intramedullary schwannomas are predominantly located in the cervical region, followed by the thoracic region and the lumbar cord ( 11 , 12 ); the conus medullaris is rarely involved. According to the location in the cross-section of the spinal cord, intramedullary schwannomas can be divided into three types: Central, surfacing and exophytic ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…A central-type tumor with no association to the posterior nerve root is considered to be a congenital neoplasm, which consists of ectopic Schwann cells originating from the embryonic neural ridge during closure of the neural tube at the fourth week ( 13 , 14 ). Pain is always the initial symptom ( 12 ), and sensory and motor dysfunction appear in the late stages of the disease.…”
Section: Discussionmentioning
confidence: 99%